Fictional Orality and Identity: The Case of Chabela in Hurricane Season by Fernanda Melchor - Bernal, Nathaly (Universidad Pedagógica y Tecnológica de Colombia, 2023)
This paper studies the fictional orality in Chabela’s direct speech, a character in Hurricane Season (2017), by Fernanda Melchor, and how it contributes to the configuration of the character’s identity. To this end, we focus on Chapter V of the novel, which is based on dialogues between Chabela and Norma. We have considered several studies on spoken colloquial Spanish (Briz Gómez; Gaviño Rodríguez; Narbona Jiménez), in order to present a classification of colloquial strategies employed by Chabela, in the syntactic, lexical-semantic, and pragmatic-contextual levels of language. It is concluded that a more or less stable set of colloquial elements is employed for the configuration of the character. Finally, based upon the concept of identity proposed by Charles Taylor, we conclude that Chabela’s identity has been built on her particular use of the language, at the same time it is reflected in it.